Sexual Silence in Breast Cancer Survivorship: A Secondary Qualitative Study of Healthcare Practices and Sexual Concerns - Mina Esmkhani; Charrlotte Seib; Armin Ariana (Health Science Reports, 2026)
ABSTRACT Background and Aims In routine breast cancer follow‐up care, sexual concerns are rarely discussed, shaping how women understand and respond to post‐treatment changes. This study examined how survivorship care practices influence the expression and recognition of sexual concerns among women after breast cancer treatment. Methods This study employed a qualitative secondary analysis of semi‐structured interview data from 31 women aged 32–72 years who had completed primary treatment for breast cancer in Australia between 2025 and 2026. Data were re‐analysed using a reflexive thematic analysis approach to explore how healthcare interactions, clinical practices, and institutional conditions influence the expression of sexual concerns. Reporting was guided by the Standards for Reporting Qualitative Research. Results Sexual silence was produced and normalised through routine omissions in care, fragmented pathways, and moral–cultural influences, reinforcing the marginalisation of sexual concerns. Sexual concerns were positioned as secondary to survival, limiting opportunities for discussion and support within survivorship care. Conclusion Sexual distress after breast cancer is shaped by institutional practices that determine what is addressed in care and whose concerns are heard. Improving support requires greater attention to healthcare structures, professional roles, and cultural expectations shaping post‐treatment experiences.